ECB policies effective in the euro area and Germany - Malte Rieth; Michele Piffer; Michael Hachula (DIW Economic Bulletin, 2016)
The European Central Bank has engaged in a wide range of nonstandard monetary policy measures since 2007. Each new tool was accompanied by an intense public debate on its effectiveness. This study evaluates the average effect of these measures on the macro-economy. The estimates show that unexpected changes in monetary policy that lower euro-area sovereign bond yields lead to a significant rise in real GDP, consumer prices, inflation expectations, and credit volume in the euro area. The effects on the German economy are very similar. All in all, the evaluation shows that non-standard monetary policy shocks are effective and contribute to fulfilling the central bank's mandate.
Keywords: E52; E58; E63; 330; central banks; monetary policy; inflation; structural VAR